The Copper Homeostasis Transcription Factor CopR Is Involved in H2O2 Stress in Lactobacillus plantarum CAUH2 - Yang, Yang; Yin, Jia; Liu, Jie; Xu, Qi; Lan, Tian; Ren, Fazheng; Hao, Yanling (Frontiers in Microbiology, 2017)
Transcriptional factors (TFs) play important roles in the responses to oxidative, acid and other environmental stresses in Gram-positive bacteria, but the regulatory mechanism of TFs involved in oxidative stress remain unknown in lactic acid bacteria. In the present work, homologous overexpression strains with 43 TFs were constructed in the L. plantarum CAUH2 parent strain. The strain overexpressing CopR displayed the highest sensitivity and a 110-fold decrease in survival rate under H2O2 challenge. The importance of CopR in the response to H2O2 stress was further confirmed by a 10.8-fold increase in the survival of a copR insertion mutant. In silico analysis of the genes flanking copR revealed putative CopR-binding ‘cop box’ sequences in the promoter region of the adjacent gene copB encoding a Cu2+-exporting ATPase. Electrophoretic mobility shift assay (EMSA) analysis demonstrated the specific binding of CopR with copB in vitro, suggesting copB is a target gene of CopR in L. plantarum. The role of CopB involved in oxidative stress was verified by the significantly decreased survival in the copB mutant. Furthermore, a growth defect in copper-containing medium demonstrated that CopB functions as an export ATPase for copper ions. Furthermore, EMSA assays revealed that CopR functions as a regulator that negatively regulates copB gene and Cu2+ serves as inducer of CopR to activate the expression of CopB in response to H2O2 stress in L. plantarum CAUH2. Our findings indicated that CopR plays an important role in enhancing oxidative resistance by regulating copB to modulate copper homeostasis.